The Influence of Digital Transaction Security, Product Knowledge, and Ease of Use on the Decision to Use the Byond by BSI Application : (Study on Students in Bandar Lampung) - Lia Hanisa Rahmawati; Moh Bahrudin; A Zuliansyah (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to determine the influence of digital transaction security, product knowledge, and ease of use on students' decisions to use the Byond by BSI application in Bandar Lampung. This study uses a quantitative method with primary data obtained through the distribution of questionnaires to 100 respondents. The sample used in this study is active students in universities who are in Bandar Lampung, domiciled or currently studying in Bandar Lampung and who know or use Byond by BSI. The data analysis technique uses the data analysis technique using IBM SPSS (Statistical Package for the Social Sciences) version 31 with multiple linear regression analysis. The results of the study show that digital transaction security, product knowledge, and ease of use have a positive and significant effect on students' decisions to use the Byond by BSI application. Simultaneously, all independent variables have a significant effect on the decision to use the Byond by BSI application.